The Impact of ORKÖY Activities on Sustainable Forest Management in İstanbul Province, Turkey - Daşdemir İ.; Köse, Murat (Springer Science and Business Media B.V., 2021)
ORKÖY (Forest and Village Relations) activities are carried out by the General Directorate of Forestry in Turkey in order to develop forest villages, improve forest and village relations, and reduce the pressure on forests. This study aims to investigate the impacts of ORKÖY activities on sustainable forest management in the İstanbul province of Turkey. For this purpose, the data of ORKÖY and forestry activities between 2012 and 2016 were collected from the records of the İstanbul Regional Directorate of Forestry (İRDF), and some information was gathered by means of questionnaires with forest villagers and forest enterprise managers. The data were evaluated using tables, descriptive statistics, and correlation analysis. In this study, the amount of the economic and social monetary credits given by ORKÖY department affiliated to the İRDF and their annual average economic contributions were determined. The fuelwood rent provided to forest villagers, the effectiveness and satisfaction levels with ORKÖY activities, the sufficiency of the credits, and the informational and training-consulting services were explored. The results show that ORKÖY provided a total of US$ 2,529,040 and an annual US$ 505,808 of credits to 575 households located in 126 villages of the İstanbul province during 2012–2016. ORKÖY performed 3007 informational and training-consulting activities in 129 villages and provided at least US$ 256 fuelwood subsidies per year per household for the forest villagers. The effectiveness and satisfaction level of ORKÖY activities was at the medium level in the İstanbul province. The contributions of the activities to the prevention of migration were weak, and to the prevention of unemployment were at the weak-medium level. Thus, ORKÖY activities were found to be effective and successful in rural development and sustainable forest management at the “medium” level (50 percent out of 100). In order to increase this rate, the quantity and quality of the informational and training-consulting services of ORKÖY need to be increased, and the health insurance of the government needs to be expanded to cover the rural population, and all state institutions should take responsibility to contribute to rural development.
Keywords: Forest and village relations; Forest village; Rural development; Sustainable forest management; Turkey; İstanbul